Acharacterization, Antioxidant Properties And Authentication Of Virgin Coconut Oil - Abdul Manaf, Marina (2009)

(untitled)
A study on chemical properties and authentication of virgin coconut oil (VCO) was conducted. Chemical properties showed that commercial VCO had iodine value of 4.47 to 8.55, peroxide value of 0.21 to 0.57 meq oxygen/kg, free fatty acid of 0.15 to 0.25, saponification value of 250.07 to 260.67 mg KOH/g oil and anisidine value of 0.16 to 0.49. Lauric acid was the predominant fatty acid which ranged from 46.64 to 48.03%. Major triacylglycerol (TAG) were LaLaLa, LaLaM, CLaLa, LaMM and CCLa (La:lauric; C:capric; M:Myristic) which accounted for more than 80% TAG of the oil. Total phenolic content ranged from 7.78 to 29.18 mg GAE/g oil. VCO samples exhibited higher antioxidant activity (49.79 to 79.87%) compared to refined, bleached and deodorized (RBD) coconut oil (49.58%). Comparison between different processing methods of VCO showed that VCO produced by fermentation method possessed the strongest scavenging effect on 1,1-diphenyl-2-picrylhydrazyl (DPPH) with the amount of oil necessary to decrease the initial DPPH radical concentration by 50% (EC50) value of 1.24 mg/mL. VCO produced by fermentation method also exhibited the highest antioxidant activity of 71% while the highest reducing power of VCO produced by chilling method was 1.02 at 10 mg/mL. The results revealed that VCO produced by both fermentation and chilling method had higher antioxidant potency than RBD coconut oil. Total phenolic content was strongly correlated with radical scavenging capacity (r = 0.91) and reducing power (r = 0.96) while no correlation was observed for β-carotene bleaching test. Some phenolic acids found in VCOs were protocatechuic, vanillic acid, caffeic acid, syringic acid, coumaric acid and ferulic acid. Rapid methods were developed to detect adulteration in VCO. First, Fourier transform infrared (FTIR) spectroscopy was used to detect adulteration of VCO with palm kernel olein. The results showed that FTIR was capable of detecting adulteration down to 1% adulteration level. Discriminant analysis using 10 principal components was able to classify pure and adulterated samples on the basis of their spectra. A partial least square (PLS) calibration demonstrated a good linear regression (R2) of 0.9875 of actual value against FTIR predicted concentration of palm kernel olein. Discriminant analysis was also capable to distinguish between VCO and other vegetable oils.Another rapid method, differential scanning calorimetry (DSC) was also used to determine adulteration of VCO with selected vegetable oils, namely soybean oil (SBO) from linolenic acid group, sunflower oil (SFO) from oleic-linoleic acid group and palm kernel oil (PKO) from lauric acid group. The heating curves of SBO and SFO adulterated samples demonstrated adulteration peaks appearing at the lower temperature region starting at 10% adulteration level. Regression analysis using stepwise multiple linear regressions (SMLR) was used to predict the percent of adulterant with R2 of 0.9390 for SFO and 0.9490 for SBO. No adulteration peak was observed for PKO adulterated oils but a good relationship between the main exothermic peak height of PKO and percentage of adulteration was established with R2 of 0.9454. Finally, electronic nose with surface acoustic wave (SAW) sensor was used to detect adulteration in VCO with palm kernel olein. Qualitative analysis was made possible using VaporPrintTM, which translated the sensor’s response into visualized two dimensional image. Adulteration peaks were identified from chromatogram profile and the best relationship (R2 = 0.9093) was obtained between adulterant peak F and the percentage of palm kernel olein added. Pearson correlation (r) of 0.92 was obtained between adulterant peak F and iodine value while correlation (r) of 0.89 was obtained between peroxide value and adulterant peak F. Principal component analysis (PCA) provided good separation of samples with 74% of the variation accounted for principal component 1 and 17% accounted for principal component 2. Excellent result was obtained in the differentiation of pure and adulterated samples down to 1% detection limit. In conclusion, this study provides references on chemical properties as well as presented the antioxidative potential of VCO. New methods were also developed for detection of adulteration of VCO with other oils using rapid analytical techniques.